Media Convergence and Human Resources Management in Sport Media Newsroom - Case Study at Daily TopSkor - Narayana Mahendra Prastya (Ikatan Sarjana Komunikasi Indonesia, 2017)
Nowadays, media companies cannot avoid the demand of media convergence. Media companies needs to make adjustments in human resources management (HRM), in order to gain success in media convergence. One unit that need for adjustment is the newsroom. This study aims to find out how HRM in the newsroom of TopSkor Sport Daily Newspaper to deal with the challenge of media convergence. TopSkor was chosen as a research object because it offers a wealth of sports information in different platforms: printed and online. TopSkor has experience for more than a decade as sport print media; but its status is a new comer in the online sport media competition. The results show that the activities of HRM by TopSkor newsroom are: developing the ability for their journalists, adding job obligations for their journalists, and recruiting new personnels for the online version.